DESIGN OF RAILWAY WHEEL PROFILE USING OPTIMIZATION TECHNIQUE - Shevtsov, I. Y.; Markine, V. L.; Esveld, C. (Science and Transport Progress, 2004)
A wheel tread design procedure has been developed. The procedure is based on the geometrical characteristics of hie wheel and rail contact. Using the numerical optimization technique we have got a wheel tread with the contact geometrical characteristics that were determined in advance. It has been show that the obtained wheel tread can reduce wheel and rail wear not worsening the dynamic characteristics. The latter, property has been analyzed with the hel the computation package ADAMS/Rail.